Carcass characteristics and valuable cuts of slaughtered dairy and beef cows from seven different breeds - Huuskonen, Arto; Mikkola, Jarmo; Manni, Katariina (Scientific Agricultural Society of Finland, 2025)
The objective of the present study was to determine carcass traits of dairy and beef breed cows in the Finnish cattle population. The data collected from a Finnish slaughterhouse included observations of 7 522 Holstein (HO), 6 367 Nordic Red (NR), 422 Limousin (LI), 180 Hereford (HF), 119 Simmental (SI), 117 Angus (AB), and 93 Charolais (CH) cows. The carcasses were graded for conformation and fat score in accordance with the EU beef carcass classification scheme (EUROP) on a continuous 15-point scale. The NR dairy cows had better conformed and fatter carcasses compared to HO cows (p< 0.001) but the yields of tenderloin, inside round and roast beef were higher in HO compared to NR cows (p< 0.01). In beef cows, British breeds (AB, HF) had lower conformed carcasses and higher yield of surface fat compared to Continental breeds (CH, LI, SI) (p< 0.05). Slaughter weight of HO and NR cows was positively correlated to carcass conformation score, carcass fat score and surface fat yield. The yields of tenderloin, inside round and roast beef decreased in both breeds as slaughter weight increased. Slaughter weight had no effect on loin and entrecote yields.
Keywords: naudanliha; rodut (eläimet); lypsykarja; lihakarja; ruhot; beef production; carcass weight; carcass conformation; carcass fatness